Health-related quality of life in Thai patients with hepatocellular carcinoma and its influencing factors: A cross-sectional study - Pathomjaruwat, Thitiporn; Matchim, Yaowarat; Armer, Jane M. (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Health-related quality of life (HRQoL) is a critical indicator in individuals with cancer. Patients diagnosed with hepatocellular carcinoma (HCC) commonly experience a decline in HRQoL due to both the progression of the disease and the adverse effects associated with treatment. Despite the high prevalence of HCC in Thailand, there is a paucity of research examining the HRQoL of Thai patients and the factors that may influence it. Objective: This study aimed to examine HRQoL in Thai patients with HCC and evaluated the relationships between disease stage, comorbidities, albumin level, functional status (FS), self-management behaviors (SMBs), and HRQoL. Methods: A correlational, cross-sectional study was conducted with 408 patients with HCC recruited from six hospitals in central Thailand between April and September 2024. Data collection included demographic and clinical information, along with the Functional Assessment of Cancer Therapy-Hepatobiliary (FACT-Hep) scale, Inventory of Functional Status-Cancer (IFS-CA), and the SMB scale for patients with HCC. All instruments were validated and reliable. Data were analyzed using descriptive statistics and multiple regression analysis. Results: Most participants were at intermediate (38.97%) or advanced (24.26%) stages of HCC. Overall HRQoL was high (mean FACT-Hep score = 147.92 ± 26.09). Disease stage, comorbidities, albumin level, FS, and SMBs were all significantly correlated with HRQoL (r = 0.771). Together, these factors explained 58.9% of the variance in HRQoL (adjusted R² = 0.589, F(5, 402) = 117.745, p <0.001). Significant predictors of HRQoL included disease stage (β = -0.116), comorbidities (β = -0.080), albumin level (β = 0.278), FS (β = 0.388), and SMBs (β = 0.296). Among these, FS was the strongest predictor. Conclusion: Improving self-management behaviors, functional status, and nutritional status shows promise for enhancing HRQoL in patients with HCC. These findings can guide nurses in developing interventions to support patients with HCC and improve their quality of life.